2018
DOI: 10.1007/s11469-018-9937-1
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction, Fatigue, and Sleep Problems Among Adolescent Students: a Large-Scale Study

Abstract: Aim:The aim of the present study was to examine the association between Internet Addiction (IA), fatigue, and sleep problems among university students.Methods: A total of 3,000 Turkish students aged 18 to 25 years were approached and 2,350 students (78.3%) participated in this cross-sectional study from April 2017 to September 2017 in public and private universities in Istanbul. Data were collected via a structured questionnaire including socio-demographic details, lifestyle and dietary habits, Internet Addict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
56
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 40 publications
10
56
1
2
Order By: Relevance
“…Being single (e.g., unmarried, divorced, separated, widowed) has also been identified as a risk factor for IA but this was not found in the present study (although the majority of individuals in the present study were not in a relationship). Studies have also suggested a strong association between IA and poor sleep (Afrin et al 2017;Bener et al 2018;Bener and Bhugra 2013;Islam and Hossin 2016). However, the present study found no such association.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Being single (e.g., unmarried, divorced, separated, widowed) has also been identified as a risk factor for IA but this was not found in the present study (although the majority of individuals in the present study were not in a relationship). Studies have also suggested a strong association between IA and poor sleep (Afrin et al 2017;Bener et al 2018;Bener and Bhugra 2013;Islam and Hossin 2016). However, the present study found no such association.…”
Section: Discussioncontrasting
confidence: 77%
“…Using the internet more than 5 h daily has been designated as an important risk factor for IA although excessive use can simply be a function of educational and/or occupational activity (Griffiths 2010;Laconi et al 2018;Salehi et al 2014) and on its own is not necessarily an indicator of problematic use (and excessive use is also not necessarily problematic). Young (2007) suggested that using the internet for more than 38 h a week may result in addiction, similar to Bener et al (2018) who suggested 35 h a week. However, such simple time indicators have been criticized as not taking the context of internet use into account (Griffiths 2010).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Research by Song et al (2010) reported that internet addiction among adolescents was correlated with depression and sleep problems. Many studies have reported that increased time spent on the internet significantly disrupts sleep-wake schedules and that heavy internet users experience high levels of insomnia (e.g., Bener et al 2019;Choi et al 2009;Jenaro et al 2007;Rotunda et al 2003;Thomée et al 2007). Cheung and Wong (2011) found that both insomnia and internet addiction were associated significantly with depression.…”
mentioning
confidence: 99%
“…Examples of all possible equivalence testing outcomes from RCTs published in Addiction (panels 1, 3, & 4) & a recent study published in International Journal of Mental health & Addiction (panel 2; no example of this outcome could be identified in trials published in Addiction, likely because this finding typically requires very large sample sizes & small effects)[1]Lintzeris et al (2002), comparison of self-reported heroin use after 8 days between intervention (buprenorphine) & control groups; [2]Bener et al (2019), difference between students with internet addiction disorder (1) vs. "normal" students(2)on question 4 of the 14-item Fatigue Scale ("Do you have problems starting things? "); [3] Petrakis et al (2017), comparison of mean no.…”
mentioning
confidence: 99%